A critical review on lead removal from industrial wastewater: Recent advances and future outlook. (February 2022) - Kumar, Vinay; Dwivedi, S.K.; Oh, Seungdae
Abstract: Lead pollution has taken immense consideration of the industrialists, environmentalists, policymakers and health workers due to its public health concerns. The wastewater generated from the industries has a noteworthy role in lead (Pb(II)) contamination to the environment. In addition to human health concerns, Pb(II) has a considerable dilemma on the vegetation and fauna of the environment and can inadequately manipulate the intact ecosystem due to its terrible toxicity after getting contaminated with Pb(II). Researchers have explored several ways to combat to Pb(II) contamination problem. The entire techniques explored at present are not suitable in the aspects of "sustainability" and "eco-friendliness" and thus "cleaner strategies" are going to be dominated over other techniques in shortly noon. This aspect is lacking in the literature and hence covered in this review to ease the difficulties of the industrialists, environmentalists and policymakers in finding such cleaner and ecofriendly techniques. Thus, we primarily intended to emphasize the cleaner and advanced techniques for treatment of Pb(II) containing industrial wastewater therefore, cleaner and advanced techniques including integrated/combined technologies are critically discussed in this review. The recent development in the cleaner strategies has also been explained well. The Pb(II) water contamination sources and its toxicity to human health and plants are also elucidated in this paper for a healthier understanding of Pb(II) contagion annoyance. Graphical abstract: Unlabelled Image Highlights: Industrial wastewater is the main sources of Pb(II) contamination of natural water bodies. Cleaner strategies have been reviewed for Pb(II) removal from wastewater. Electro-active, adsorption and biological processes have high applicability for Pb(II) removal. Integrated techniques posses excellent Pb(II) removal performance from wastewater.